Student Life at the College of The Bahamas: The Role of COBUS - Cartwright, DeAndra V. (International Journal of Bahamian Studies, 2015)
Student government and student activities at the College of The Bahamas have helped to define the growth and development of the institution. The College of the Bahamas Union of Students or COBUS as it is better known, has been a crucible for civic and professional leaders. Many COBUS Presidents have gone on to become leaders in the community, well-known forerunners in their respective fields of endeavour and have become household names in the Bahamas.